HUBUNGAN STATUS NUTRISI TERHADAP OUTCOME KLINIS PASIEN SIROSIS HATI DI RSUD DR. SAIFUL ANWAR MALANG - Supriono, Supriono; Dianita Mayasari , Ema (RSUD Dr. Saiful Anwar Province of East Java, 2023)
Introduction: Nutritional status is often associated with mortality and disease morbidity, including liver cirrhosis. Assessment of Tricep Skin Fold (TSF) and mid-arm muscle circumference (MAMC) is an easy parameter of nutritional status. Objective: This study aims to determine the relationship between nutritional status and clinical outcomes in patients with liver cirrhosis. Methods: The study used a retrospective cohort observational design with a sample of 57 patients with liver cirrhosis with various etiologies. The data comes from the results of anthropometric measurements of patients in the poly or inpatient ward and interviews regarding the history of the disease and complications experienced during the last month. Data analysis used the Chi-square test with a 95% Confidence Interval (CI), p < 0.05, to analyze the relationship between nutritional status (TSF and MAMC) with clinical outcomes of liver cirrhosis (hematemesis melena, degree of esophageal varices grade Hepatic encephalopathy (HE) and degree of ascites). Results: Based on the TSF and MAMC values, data on cirrhotic patients who experienced nutritional status with the “low” criteria were 33.3% and 57.89%, respectively. The 'low” TSF value significantly correlates with the HE incidence (p = 0.049) with the RR value of 0.461. The relationship between MAMC and the incidence of ascites was statistically significant (0.004), with an RR value of 0.462. Conclusion: Nutritional status affects the incidence of HE and ascites in liver cirrhosis patients